FAILURE ANALYSIS OF OIL COLLECTING BOX CONNECTING PIN IN 1580MM HOT ROLLING MILL - TONG JinYu; BAO JiaHan; ZHENG JinDe; PAN ZiWei; ZHU XiaoLong; ZHA CongWen; HU Biao; HE FuJin (Jixie qiangdu)
In order to solve the problem of multiple failures of the oil collecting box connecting pin of the arc gear toothed when the 1580 mm hot strip mill F2 rolling mill was rolling the thin plate,several field tests were performed on the F2 rolling mill drive system and roll system,and the test signal was processed in time domain and frequency domain. The three-dimensional finite element model of rolling mill was built to simulate the natural frequency of the vibration,including main drive system,roller system and frame. The calculated results are basically consistent with the test results. It can be determined that the mill unit has a resonance and the dominant frequency corresponds to the maximum vibration displacements are found at the side of the gear box,providing an effective reference for further analysis of the mill vibration characteristics and causes.